DEVELOPMENT OF TEACHING MATERIALS BASED ON LOCAL POTENTIALS ABOUT FORCE TO FOSTER THE ENTREPRENEURSHIP FOR FOURTH GRADE STUDENTS OF SD NEGERI KEMIRI - Tiyara Mahardini; Kartika Chrysti Suryandari; Tri Saptuti Susiani (Universitas Sebelas Maret, 2022)
The study aimed to analyze the feasibility and the effectiveness of teaching materials to improve natural science leaning outcomes about style to foster the entrepreneurship for fourth grade students of SD Negeri Kemiri in academic year of 2019/2020. It was Research and Development (RnD). Development model or 4-D model was developed by Thiagarajan, Semmel, and Semmel (1974). The subjects were a teacher and students of SD Negeri Kemiri. The data were quantitative and qualitative. Data collection instruments used interviews, observations, questionnaires, and tests (pre-test and post-test). The data analysis techniques were descriptive analysis, prerequisite analysis test (normality test and homogeneity test), and effectiveness test of teaching materials (N-gain and effect size). The results indicate that the teaching materials based on local potential about style have feasibility for learning, improve leaning outcomes, and foster the entrepreneurship.